El liderazgo en la gestión administrativa del Colegio Fiscal ‘Eduardo Salazar Gómez’ - Broncano Urbano, Deisy Silvana (2022)
Leadership represents the activity of the director, aimed at combining the institutional mission with the people of the educational organization, generating pedagogical transformations that involve effective communication and organization, establishing direction, motivating all social entities in this way creates an environment that directs the school towards a transformation and quality improvements, where educational and administrative management is maximized. However, in the 'Eduardo Salazar Gómez' Fiscal College, weaknesses and potentialities were observed that need to be addressed by formulating the following research problem: How does leadership affect the administration of the 'Eduardo Salazar Gómez' Fiscal College, that is why The objective of this study is to develop a leadership training program to improve the administrative management of the 'Eduardo Salazar Gómez' Fiscal College; where the epistemological foundation focused on the concepts on the subject, for which a training program was designed and applied to help strengthen it, which was developed under the methodology used with a quantitative approach with field type and documentary film. The method used was deductive, and as collection instruments a structured interview, concluding an increase in leadership in administrative management.